Closing the data gap: A model for national-level food loss and waste data generation in the absence of existing data - Soethoudt, J.M. (CGIAR Initiative on Low-Emission Food Systems, 2024)
In the UN many countries committed themselves to reduce FLW towards 20301. So-called national pathways are developed, written by governments, elaborating on how this will be established. In order to support and validate these efforts, FLW monitoring2 is required on national level. This is a complex task for LMIC, since it is difficult to get data from rural and remote areas. In addition, the variety in products, supply chain links (SCLs), climatic conditions (weather, water, soil) increases the workload of any monitoring approach dramatically.